Symbolic Threat Mediated Collective Narcissism and Antisemitic Conspiracy Belief - Rikardi, Audi Ahmad; Zein, Rizqy Amelia (Universitas Muhammadiyah Surakarta, 2025)
This study aimed to analyze the mediating role of symbolic threat in the relationship between collective narcissism and belief in antisemitic conspiracy theories. The Jewish community in Indonesia is almost nonexistent, yet antisemitic conspiracy theories are relatively widespread. Jews have been used as scapegoats in events that had significant global impact and are often perceived as a threat through symbols associated with them. A bootstrapped mediation analysis with 5,000 iterations was conducted to examine the role of symbolic threat as a mediator between collective narcissism and belief in antisemitic conspiracy theories. Participants were recruited online, and 385 respondents (Mage = 21.57) completed the belief in Jewish conspiracy theory scale, the collective narcissism scale, and the symbolic threat scale. The analysis revealed that symbolic threat significantly mediated the relationship between collective narcissism and belief in antisemitic conspiracy theories (B = 0.51, SE = 0.06, CI95% = 0.40–0.62, p < .001). Individuals with higher levels of collective narcissism tended to perceive Jews as symbolic threats, which in turn predicted stronger belief in antisemitic conspiracy theories. This study demonstrated how symbolic threat contributes to conspiratorial belief formation and provided empirical evidence on antisemitic attitudes in Indonesia. Furthermore, the findings contributed to extending intergroup relations discourse regarding perceptions of Jews in Southeast Asia.